2019
DOI: 10.1016/j.ibmb.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution QTL mapping in Tetranychus urticae reveals acaricide-specific responses and common target-site resistance after selection by different METI-I acaricides

Abstract: Arthropod herbivores cause dramatic crop losses, and frequent pesticide use has led to widespread resistance in numerous species. One such species, the two-spotted spider mite, Tetranychus urticae, is an extreme generalist herbivore and a major worldwide crop pest with a history of rapidly developing resistance to acaricides. Mitochondrial Electron Transport Inhibitors of complex I (METI-Is) have been used extensively in the last 25 years to control T. urticae around the globe, and widespread resistance to eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
111
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(121 citation statements)
references
References 87 publications
4
111
1
Order By: Relevance
“…Target‐site mutations associated with acaricide resistance in T. urticae have been discovered in genes encoding: (a) acetylcholinesterase ( AChE ), which is associated with resistance to organophosphates and carbamates; 32 (b) voltage‐gated sodium channel ( vgsc ), which confers resistance to pyrethroids; 16,27,29 (c) glutamate‐gated chloride channels ( GluCl1/3 ), which are linked with resistance to abamectin; 30,31 (d) cytochrome b ( cytb ), which is associated with bifenazate and acequinocyl resistance; 26,40 (e) chitin synthase 1 ( chs1 ), which has been linked with high levels of resistance to the mite growth inhibitors (MGIs) etoxazole, clofentezine and hexythiazox; 22,41 (f) PSST subunit ( psst/NDUFS7 ) of mitochondrial respiratory complex I, which has been associated with resistance to pyridaben, tebufenpyrad and fenpyroximate; 9,42 and (g) succinate dehydrogenase subunits B and C ( SdhB and SdhC , respectively) conferring resistance to several complex II inhibitors 43 …”
Section: Introductionmentioning
confidence: 99%
“…Target‐site mutations associated with acaricide resistance in T. urticae have been discovered in genes encoding: (a) acetylcholinesterase ( AChE ), which is associated with resistance to organophosphates and carbamates; 32 (b) voltage‐gated sodium channel ( vgsc ), which confers resistance to pyrethroids; 16,27,29 (c) glutamate‐gated chloride channels ( GluCl1/3 ), which are linked with resistance to abamectin; 30,31 (d) cytochrome b ( cytb ), which is associated with bifenazate and acequinocyl resistance; 26,40 (e) chitin synthase 1 ( chs1 ), which has been linked with high levels of resistance to the mite growth inhibitors (MGIs) etoxazole, clofentezine and hexythiazox; 22,41 (f) PSST subunit ( psst/NDUFS7 ) of mitochondrial respiratory complex I, which has been associated with resistance to pyridaben, tebufenpyrad and fenpyroximate; 9,42 and (g) succinate dehydrogenase subunits B and C ( SdhB and SdhC , respectively) conferring resistance to several complex II inhibitors 43 …”
Section: Introductionmentioning
confidence: 99%
“…Park et al found that ABCC transporters were involved in the resistance of S. exigua to Bt toxins through bulk segregant analysis (Park et al, 2014). To study non-monogenic resistant trait, Snoeck et al applied high-resolution QTL mapping to localize target genes related to the resistance of T. urticae to METI-I acaricides; a PSST homologue, cytochrome P450 reductase, and nuclear hormone receptor 96 were identified (Snoeck et al, 2019). In the future, whole genome resequencing for P. citri will be performed to localize resistant genes response to amitraz in mites.…”
Section: Discussionmentioning
confidence: 99%
“…The haplodiploid spider mite Tetranychus urticae is a major global agricultural pest which rapidly develops resistance to pesticides of various modes of action [34]. As revealed by recent studies, T. urticae is highly amenable to BSA genetic mapping, with QTL, including for quantitative pesticide resistance, narrowed to small genomic intervals that have suggested specific candidate genes and causal alleles [29,33]. In some instances, known causal variants were recovered [3538], confirming the validity of the narrow genomic intervals identified by BSA studies using large, highly replicated T. urticae experimental populations [25].…”
Section: Introductionmentioning
confidence: 99%